Strategies for teaching postural habits to children: comic strips vs. practical experience (Fisioterapia e Pesquisa, 2009)
This experimental study assessed the effects of a posture education program comparing two teaching strategies: by means of a comic strip (CS) and through practical experience (PE), in which children experienced each correct and incorrect posture. The posture education program was applied to 2nd- and 3rd-grade students aged 7-to-11 in three teaching meetings. The sample consisted of 40 boys and 40 girls evenly distributed into two groups, each taught by one teaching strategy: CS group and PE group. Questionnaires were applied before program onset and six months after the end of the program, in order to assess participants' postural habits. Correct postures taught were standing, sitting, knapsack carrying, bending down, moving objects, and sleeping posture. Results showed significant improvement in learning and memorizing correct postures by all subjects; no significant differences were found between the groups in all variables assessed. Both comic strip and practical experience teaching strategies were thus efficient in teaching boys and girls healthy postural habits.